Fuzzy Model for the E-Tourism Digital Platform Quality Assessment - Irina SHPOLIANSKAYA; Alexei DOLZHENKO; Nikita STEPANOV; Leonid POTAPOV (Communications of International Proceedings, 2021)
In the modern world of communication and information, a company cannot improve and be competitive on a global or even local level without modern digital technologies. The development of information and communication technologies in the tourism industry has led to the emergence of e-tourism. Information networks, web and mobile technologies, dynamic systems of interaction with consumers and partners, big data processing technologies are crucial for creating prerequisites and enabling the active development of the tourism business. Web technologies provide tourism businesses with new opportunities to organize more effective interactions with partners and consumers of travel-related services. E-tourism digital platforms are becoming a single point of interaction for all categories of interested users, both tourists, and businesses providing tourist services. The main problem that limits the possibility of widespread use of digital platforms as an effective tool for e-business and marketing in the tourism industry is the lack of procedures for assessing the platform quality, both at the design stage and during its operation. The article describes a model for the e-tourism platform quality assessment using expert methods and fuzzy logic in terms of the possibilities of effective promotion of tourist services.
Keywords: E-Tourism; Digital Platform; Quality Evaluation; Fuzzy Model.